Cognitive-behavioural integrated treatment (C-BIT) : a treatment manual for substance misuse in people with severe mental health problems - Graham, Hermine L. (J. Wiley, 2004)
This exciting new book addresses the important issue of how to provide integrated mental health and substance misuse treatment of individuals with these co-occurring disorders. Combining both theory and practice, by the use of illustrative clinical case material, it provides a survey of different approaches to the integration of mental health and substance misuse services.